Reconstructing the Philosophical Foundation of Education : A Three Tiered Integrative Model in the Contemporary Era - Ibadullah; Neng Julia; Abdullah; Badrudin; Machdum Bachtiar (MA'ALIM: Jurnal Pendidikan Islam, 2026)
In the contemporary era, modern educational systems are heavily challenged by a utilitarian paradigm that overemphasizes cognitive and technical achievements, leading to a pervasive dichotomy of knowledge and moral degradation among students. This study aims to address these deficiencies by reconstructing the fundamental philosophy of education through a systematic conceptual synthesis. Employing a qualitative method with a library research approach, this study critically analyzes authoritative texts specifically focusing on the seminal works of Ramayulis and Abuddin Nata as primary benchmarks to establish rigorous conceptual criteria for educational philosophy. The findings introduce a novel, three tiered integrative matrix that redefines the relationship between general thought and educational policy. In this hierarchical framework: (a) General Philosophy serves as the foundational baseline for critical thinking; (b) Philosophy of Education operates as the functional instrument for curriculum development; and (c) Islamic Philosophy of Education acts as the overarching transcendental value system that anchors the ultimate goals of education. By shifting the paradigm from a purely rational-empirical domain to a comprehensive framework that integrates divine revelation, reason, and human experience, this model offers a distinct methodology to reconstruct the concepts of Insan Kamil and Ulul Albab within modern schools. This study concludes that the three tiered model provides a robust, non-dichotomous framework necessary to cultivate an education system that balances intellectual competence with profound spiritual and character development.